2019
DOI: 10.3390/cryst9030149
|View full text |Cite
|
Sign up to set email alerts
|

On Crystal Mosaicity in Single Crystal Ni-Based Superalloys

Abstract: In the present work, we investigate the evolution of mosaicity during seeded Bridgman processing of technical Ni-based single crystal superalloys (SXs). For this purpose, we combine solidification experiments performed at different withdrawal rates between 45 and 720 mm/h with advanced optical microscopy and quantitative image analysis. The results obtained in the present work suggest that crystal mosaicity represents an inherent feature of SXs, which is related to elementary stochastic processes which govern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 67 publications
5
36
0
Order By: Relevance
“…Otherwise, the force directing effect may increase the α angle. Similar “deflections” processes are described in [30] as “re-emerging”. The authors suggest that the “re-emerging” process may reduce the degree of mosaicity because the short dendrites in the thin-walled areas bend less than the long dendrites in the thick-walled areas due to geometrical constraints [30].…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Otherwise, the force directing effect may increase the α angle. Similar “deflections” processes are described in [30] as “re-emerging”. The authors suggest that the “re-emerging” process may reduce the degree of mosaicity because the short dendrites in the thin-walled areas bend less than the long dendrites in the thick-walled areas due to geometrical constraints [30].…”
Section: Resultsmentioning
confidence: 54%
“…Similar “deflections” processes are described in [30] as “re-emerging”. The authors suggest that the “re-emerging” process may reduce the degree of mosaicity because the short dendrites in the thin-walled areas bend less than the long dendrites in the thick-walled areas due to geometrical constraints [30]. The description of mosaicity creation in the thin-walled area should include not only the length of dendrites, but also the angle between the stems of dendrites and a mould wall.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Recently, research on the dendritic array formation in the SX casts has been found to be extremely important [28]. Since the mechanisms of the dendrite growth from the selector to the root of the blade are related to the enlargement of the crystallization front cross-section, they have some features similar to the dendritic growth in the platforms [29].…”
Section: Introductionmentioning
confidence: 99%